IMPLEMENTASI PERATURAN DAERAH KABUPATEN JEPARA NOMOR 2 TAHUN 2014 TENTANG PEMBERDAYAAN, PERLINDUNGAN, DAN PEMBINAAN INDUSTRI MEBEL DI - Bayu Adytiya Candra; Margaretha Suryaningsih (Journal of Public Policy and Management Review, 2018)
Almost 75 percent of the people of Jepara work in the furniture industry, so that Jepara District get the icon and known as "Kota Ukir". For maintain the existence and to increase productivity of the furniture industry, the Government of Jepara District issued a Regional Regulation of Jepara District Number 2 year 2014 about Protection, Empowerment, and Development of Furniture Industry. This research is designed to explain how the Implementation of Regional Regulation of Jepara District Number 2 Year 2014 about Protection, Empowerment, and Development of Furniture Industry and the factors that become the incentive and resistors in the process of policy implementation that using the van Meter and Van Horn Theory. This research uses descriptive qualitative research method with data collection technique of interview, observation and documentation. Based on the results of research, the implementation of the regional regulation is still efforted by the goverment. This thing marked by the education, training and guidance that has been done to the actors of furniture business. There are aspect which was considered to the regional regulation, one of the aspect is protection, such as facilities and infrastructure that supporting the furniture industry (raw materials) and the provision of legal assistance which marked by the lack of public’s understanding about “Indikasi Geografis”. Other inhibiting factors are in the resources, and social political and economic conditions where there are still many public who are not aware of the existence of the regulation. The researcher recommends that socialization be done thoroughly to the public and the implementor so that later this policy can run optimally.